A new millipede species of the genus Gnomognathus Attems, 1942 (Diplopoda, Spirostreptida, Harpagophoridae) from South India - Sudhakaran, Nikhila; Kuruvila, Manju Elizabeth (Zootaxa, 2025)
A new species of the genus Gnomognathus Attems, 1942, is described from the Western Ghats regions of the state of Kerala, India. Gnomognathus dhoni sp. nov. is distinguished from its congeners by the differences in overall gonopodal morphology and particularly by the shape and position of the tibial spines on the telopodite. Two other species, G. macracanthus (Carl, 1941), and G. interfectus (Carl, 1941), previously thought to be restricted to Tamil Nadu, have been recovered from Kerala. The genus now comprises nine species. A key is proposed for all species of the genus based on the gonopodal characters along with a concise comparison of contrasting characters and a distribution map.